Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2208339
|View full text |Cite
|
Sign up to set email alerts
|

Dwell-and-spring

Abstract: In graphical user interfaces, direct manipulation consists in incremental actions that should be reversible. Typical examples include manipulating geometrical shapes in a vector graphics editor, navigating a document using a scrollbar, or moving and resizing windows on the desktop. As in many such cases, there will not be any mechanism to undo them, requiring users to manually revert to the previous state using a similar sequence of direct manipulation actions. The associated motor and cognitive costs can be h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, rare exceptions exist of authors who consider how to alleviate this problem, although not always with explicit reference to the concept of discoverability. These considerations take the form of either attempting to make proposed novel interaction methods discoverable from the beginning [8,9,37,43,123] or improving the discoverability of existing features and input methods [43,72,81,82,111]. Additionally, existing designs are compared and evaluated [39,59,111], adapted design procedures are suggested [19] and study methodologies proposed [24,26] in an effort to improve discoverability.…”
Section: Research Addressing Discoverabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, rare exceptions exist of authors who consider how to alleviate this problem, although not always with explicit reference to the concept of discoverability. These considerations take the form of either attempting to make proposed novel interaction methods discoverable from the beginning [8,9,37,43,123] or improving the discoverability of existing features and input methods [43,72,81,82,111]. Additionally, existing designs are compared and evaluated [39,59,111], adapted design procedures are suggested [19] and study methodologies proposed [24,26] in an effort to improve discoverability.…”
Section: Research Addressing Discoverabilitymentioning
confidence: 99%
“…For example, [8,9] introduced the novel undo mechanism Dwelland-Spring and considered whether users would discover the technique. They found a lower discovery rate than expected and concluded that there may be a trade off between the stronger feedforward required to improve discovery and the design aim of making the mechanism easy to discard.…”
Section: Research Addressing Discoverabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The band shows the trace of an ongoing manipulation to help users trace their edits and easily cancel them, e.g., by pressing ESC. Our implementation resembles the Dwell-and-Spring technique [8] and serves as the base for all tools in the sketcher (see Fig. 6) by coupling direct manipulation with crossing-based selection [7].…”
Section: Drawing Replicating Grouping and Linkingmentioning
confidence: 99%